Low-viscosity high-strength two-component polyurethane heat-conducting pouring sealant and preparation method thereof
Patent Information
- Application Number
- CN202611254483.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-18
- Publication Date
- 2026-10-27
AI Technical Summary
聚氨酯灌封胶因其优异的柔韧性、粘接性和工艺适应性而被广泛应用,但传统聚氨酯材料存在导热系数低[通常低于0.3W/(m·K)]、机械强度一般、黏度偏高等问题,难以满足高端电源模块、逆变器、车用电机控制器等器件的严苛要求
(1)本发明通过多异氰酸酯、低黏度聚醚多元醇B、刚性增强多元醇、扩链剂以及经表面改性的球形氧化铝之间的多元协同复配,各组分在反应活性、柔韧性、刚性链段及无机填料界面相容性上形成精准匹配,有效平衡了体系内聚强度与流动性能,使灌封胶在未稀释状态下即实现≤2100 mPa·s的低施工黏度,便于真空脱泡和大规模自动化灌封作业。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to a low-viscosity, high-strength two-component polyurethane thermally conductive potting compound and its preparation method, belonging to the field of polyurethane material technology. Background Technology
[0002] As electronic components evolve towards higher integration and higher power density, heat dissipation becomes an increasingly prominent issue. Potting compounds not only need to provide electrical insulation and mechanical protection but also require excellent thermal conductivity to effectively transfer heat and prevent localized overheating. Polyurethane potting compounds are widely used due to their excellent flexibility, adhesion, and process adaptability. However, traditional polyurethane materials suffer from low thermal conductivity (typically below 0.3 W / (m·K)), moderate mechanical strength, and relatively high viscosity, making it difficult to meet the stringent requirements of high-end power modules, inverters, automotive motor controllers, and other devices.
[0003] Currently, a common method to improve thermal conductivity is to add high-filler content thermally conductive fillers (such as alumina and boron nitride). However, the addition of fillers significantly increases the viscosity of the system, reduces flowability, affects potting operations, and may also lead to a decrease in mechanical properties. Furthermore, how to achieve high strength and good resistance to humid heat aging while maintaining low viscosity has become a pressing technical challenge in the field of polyurethane potting compounds. Summary of the Invention
[0004] This invention provides a low-viscosity, high-strength two-component polyurethane thermally conductive potting compound and its preparation method, in order to solve the technical problems existing in the prior art as described above.
[0005] The technical solution provided by this invention is as follows: One objective of this invention is to provide a low-viscosity, high-strength two-component polyurethane thermally conductive potting compound, comprising component A and component B; Component A comprises the following components in parts by weight: 70-90 parts of polyisocyanate, 10-30 parts of polyether polyol A, and 0.1-0.5 parts of antioxidant; Component B comprises the following components in parts by weight: 25-45 parts of low-viscosity polyether polyol B, 10-20 parts of rigidity-reinforcing polyol, 5-15 parts of chain extender, 60-120 parts of thermally conductive filler, 0.05-0.2 parts of catalyst, and 0.1-0.5 parts of defoamer.
[0006] Based on the above technical solution, the present invention can be further improved as follows: Furthermore, the polyisocyanate is selected from at least one of liquefied diphenylmethane diisocyanate (MDI), polyphenylmethylene polyisocyanate (PAPI), and toluene diisocyanate (TDI). Furthermore, the liquefied diphenylmethane diisocyanate MDI is a carbodiimide-urea ketimide modified MDI, a carbamate modified MDI, or a prepolymer modified MDI.
[0007] Preferably, the liquefied MDI is a carbodiimide-urea ketimide modified MDI.
[0008] More preferably, the carbodiimide-urea ketimide modified MDI is Huntsman Suprasec 2020 or Wanhua MDI-100LL.
[0009] Furthermore, the polyether polyol A is selected from at least one of polypropylene oxide diol, polytetrahydrofuran ether diol, and polyethylene oxide-propylene oxide copolyether diol.
[0010] Furthermore, the molecular weight of the polyether polyol A is 600-1500.
[0011] Preferably, the polyether polyol A is polyoxypropylene glycol with a molecular weight of 700-1000.
[0012] Furthermore, the low-viscosity polyether polyol B is selected from at least one of polyoxypropylene glycol and polyoxypropylene triol.
[0013] Furthermore, the low-viscosity polyether polyol B has a molecular weight of 400-800 and a viscosity of ≤300 mPa·s at 25°C. Furthermore, the low-viscosity polyether polyol B is polyoxypropylene glycol.
[0014] Furthermore, the rigidity-reinforcing polyol is selected from at least one of bisphenol A type polyether diol, bisphenol S type polyether diol, and phthalic anhydride polyester diol. Furthermore, the bisphenol A type polyether diol is prepared by ring-opening polymerization of bisphenol A and epoxide under an alkaline catalyst; the bisphenol A type polyether diol has a molecular weight of 500-800, a hydroxyl value of 140-225 mgKOH / g, and a viscosity of 400-600 mPa·s at 25℃.
[0015] Furthermore, the chain extender is selected from at least one of diethyltoluenediamine (DETDA), dimethylthiotoluenediamine (DMTDA), and 1,4-butanediol (BDO).
[0016] Furthermore, the chain extender is diethyltoluenediamine (DETDA).
[0017] Furthermore, the thermally conductive filler is selected from at least one of spherical alumina, angular alumina, aluminum nitride, boron nitride, and zinc oxide that have been surface-treated with a silane coupling agent; the catalyst is selected from at least one of organobismuth catalysts and organotin catalysts; and the defoamer is selected from at least one of organosilicon defoamers and polyether defoamers.
[0018] Furthermore, the thermally conductive filler is a self-spherical alumina surface-treated with a silane coupling agent; the catalyst is an organobismuth catalyst; and the defoamer is an organosilicone defoamer.
[0019] Furthermore, the antioxidant is selected from at least one of antioxidant 1010 {pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]}, antioxidant 1076 [octadecyl β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], and antioxidant 168 [tris(2,4-di-tert-butylphenyl)phosphite].
[0020] Furthermore, the antioxidant is antioxidant 1010.
[0021] The second objective of this invention is to provide a method for preparing the low-viscosity, high-strength two-component polyurethane thermally conductive potting compound as described above, comprising the following steps: Preparation of component A: Under dry nitrogen protection, add polyisocyanate and antioxidant to the reaction vessel, heat to 50±5℃ and stir evenly. Under continuous stirring, slowly add polyether polyol A that has been vacuum dehydrated at 110±5℃ for 1.5-2h. After the addition is complete, raise the system temperature to 75±5℃, react for 2-3h, cool, discharge, seal and package to obtain component A. Preparation of Component B: Under vacuum conditions, low-viscosity polyether polyol B, rigid-reinforcing polyol, chain extender, catalyst and defoamer are added to a planetary mixer and stirred and mixed evenly at 60-70℃ and normal pressure. Then, thermally conductive filler is added in batches, and stirred evenly after each addition. After all the filler has been added, the planetary mixer is evacuated to -0.098MPa to -0.095MPa and stirred and mixed under vacuum for 1-1.5h. After cooling to room temperature, the material is discharged, sealed and packaged to obtain Component B. Component A and component B are mixed at a weight ratio of 1:1-3 to obtain the low-viscosity, high-strength two-component polyurethane thermally conductive potting compound.
[0022] The technical solution provided by this invention has the following advantages compared with the prior art: (1) This invention achieves a precise match between the multi-component synergistic compound of polyisocyanate, low viscosity polyether polyol B, rigid reinforcing polyol, chain extender and surface-modified spherical alumina. The components are precisely matched in terms of reactivity, flexibility, rigid chain segments and inorganic filler interface compatibility, effectively balancing the cohesive strength and flow performance of the system. This allows the potting compound to achieve a low construction viscosity of ≤2100 mPa·s in the undiluted state, which is convenient for vacuum degassing and large-scale automated potting operations.
[0023] (2) Thanks to the rigid aromatic ring structure introduced by bisphenol A type polyether diol and the high cross-linking density network formed by liquefied MDI, and the chain extender provides uniform hard segment micro-regions, the potting compound of the present invention exhibits a shear strength of ≥11.2 MPa after curing, giving electronic devices excellent impact resistance and vibration resistance reliability.
[0024] (3) The surface-treated spherical alumina is evenly dispersed in the matrix and has a strong interfacial bond. It can build an efficient thermal conduction path with a low filling amount. Combined with the low interfacial thermal resistance of the polyurethane matrix, the thermal conductivity of the cured product is ≥1.2 W / (m·K), which meets the rapid heat dissipation requirements of high-power electronic modules.
[0025] (4) The synergistic effect of each component gives the cured product excellent resistance to humid heat. Under the aging conditions of double 85 (85℃ / 85%RH), the shear strength retention rate is ≥78%, which effectively inhibits the hydrolysis of ester bonds and interface deterioration under high temperature and high humidity conditions, and significantly extends the service life of potting parts under harsh working conditions.
[0026] (5) This invention does not require the addition of organic solvents or high-cost modifying agents. The preparation process is simple and the operation window is wide. It is suitable for industrial mass production and can meet the requirements of high-power electronic devices such as new energy vehicle electronic control systems, photovoltaic inverters, and 5G base station power supplies for the comprehensive performance of potting compounds. Detailed Implementation
[0027] The principles and features of the present invention are described below with reference to examples. The examples are only used to explain the present invention and are not intended to limit the scope of the present invention.
[0028] Example 1 A low-viscosity, high-strength two-component polyurethane thermally conductive potting compound, comprising component A and component B; Component A comprises the following components in parts by weight: 80 parts of carbodiimide-urea ketimide modified MDI (NCO content approximately 29.5%, viscosity at 25°C 60 mPa·s, Wanhua MDI-100LL); 20 parts of polypropylene glycol (molecular weight 700, hydroxyl value 160 mg KOH / g, viscosity at 25°C 200 mPa·s); and 0.3 parts of antioxidant 1010. Component B comprises the following components in parts by weight: 35 parts of polypropylene glycol (molecular weight 600, hydroxyl value 187 mg KOH / g, viscosity 210 mPa·s at 25℃); 15 parts of bisphenol A type polyether glycol; 10 parts of chain extender DETDA (amine value approximately 650 mg KOH / g, viscosity 150 mPa·s at 25℃); 80 parts of commercially available spherical alumina (D50=10μm, purchased from Suzhou Sanrui Baide New Materials Co., Ltd.) surface-treated with KH-560; 0.1 parts of organic bismuth catalyst (bismuth neodecanoate, bismuth content 23%); and 0.3 parts of organosilicon defoamer (BYK-530).
[0029] The synthesis method of the bisphenol A type polyether glycol is as follows: 228 parts by weight of bisphenol A and 1.0 parts by weight of KOH are added to a high-pressure reactor. After nitrogen purging, the temperature is raised to 120°C. 116 parts by weight of propylene oxide (molar ratio of bisphenol A:propylene oxide = 1:2) are added in batches. The pressure is controlled to be ≤0.4MPa. The reaction is carried out until the pressure no longer decreases. The mixture is cooled to 80°C, neutralized with phosphoric acid, filtered to remove potassium salt, and then dehydrated under vacuum at 110°C and -0.095MPa for 2 hours to obtain bisphenol A type polyether glycol (hydroxyl value 172 mgKOH / g, molecular weight 652, viscosity at 25°C 520 mPa·s).
[0030] A method for preparing a low-viscosity, high-strength two-component polyurethane thermally conductive potting compound includes the following steps: Preparation of Component A: Under dry nitrogen protection, carbodiimide-urea ketimide modified MDI and antioxidant 1010 were added to the reactor. The temperature was raised to 50°C and stirred evenly. Under continuous stirring, polyoxypropylene glycol that had been vacuum dehydrated at 110°C for 1.5 h was slowly added dropwise. After the addition was complete, the system temperature was raised to 75°C and the reaction was carried out for 2.5 h. The mixture was then cooled to below 40°C, discharged, and sealed in packaging to obtain Component A. Preparation of Component B: Under vacuum conditions, polypropylene glycol, bisphenol A type polyether glycol, chain extender DETDA, bismuth neodecanoate and BYK-530 were added to a planetary mixer and stirred at 400 rpm for 20 min at 65 °C and atmospheric pressure. Then, commercially available spherical alumina with KH-560 surface treatment was added in batches of 20 parts each time, and stirred for 10 min after each addition. After all the additions were completed, the planetary mixer was evacuated to -0.097 MPa and stirred at 600 rpm for 1.5 h under vacuum. After cooling to room temperature, the material was discharged, sealed and packaged to obtain Component B. Component A and component B are mixed at a weight ratio of 1:1.5 to obtain the low-viscosity, high-strength two-component polyurethane thermally conductive potting compound.
[0031] Example 2 A low-viscosity, high-strength two-component polyurethane thermally conductive potting compound, comprising the following components in parts by weight: Includes component A and component B; Component A comprises the following components in parts by weight: 80 parts of carbodiimide-urea-ketimide modified MDI (NCO content approximately 29.5%, viscosity at 25°C 60 mPa·s, Wanhua MDI-100LL); 20 parts of polypropylene glycol (molecular weight 700, hydroxyl value 160 mgKOH / g, viscosity at 25°C 200 mPa·s); and 0.3 parts of antioxidant 1010. Component B comprises the following components in parts by weight: 30 parts of polypropylene glycol (molecular weight 600, hydroxyl value 187 mg KOH / g, viscosity 210 mPa·s at 25℃); 12 parts of bisphenol A type polyether glycol; 8 parts of chain extender DETDA (amine value approximately 650 mg KOH / g, viscosity 150 mPa·s at 25℃); 100 parts of commercially available spherical alumina (D50=10μm, purchased from Suzhou Sanrui Baide New Materials Co., Ltd.) surface-treated with KH-560; 0.15 parts of organic bismuth catalyst (bismuth neodecanoate, bismuth content 23%); and 0.4 parts of organosilicon defoamer (BYK-530).
[0032] The synthesis method of the bisphenol A type polyether glycol is as follows: 228 parts by weight of bisphenol A and 1.0 parts by weight of KOH are added to a high-pressure reactor. After nitrogen purging, the temperature is raised to 120°C. 174 parts by weight of propylene oxide (molar ratio of bisphenol A:propylene oxide = 1:3) are added in batches. The pressure is controlled to be ≤0.4MPa. The reaction is carried out until the pressure no longer decreases. The mixture is cooled to 80°C, neutralized with phosphoric acid, filtered to remove potassium salt, and then dehydrated under vacuum at 110°C and -0.095MPa for 2 hours to obtain bisphenol A type polyether glycol (hydroxyl value 140 mgKOH / g, molecular weight 800, viscosity at 25°C 600 mPa·s).
[0033] A method for preparing a low-viscosity, high-strength two-component polyurethane thermally conductive potting compound includes the following steps: Preparation of Component A: Under dry nitrogen protection, carbodiimide-urea ketimide modified MDI and antioxidant 1010 were added to the reactor. The temperature was raised to 50°C and stirred evenly. Under continuous stirring, polyoxypropylene glycol that had been vacuum dehydrated at 110°C for 1.5 h was slowly added dropwise. After the addition was complete, the system temperature was raised to 75°C and the reaction was carried out for 2.5 h. The mixture was then cooled to below 40°C, discharged, and sealed in packaging to obtain Component A. Preparation of Component B: Under vacuum conditions, polypropylene glycol, bisphenol A type polyether glycol, chain extender DETDA, bismuth neodecanoate and BYK-530 were added to a planetary mixer and stirred at 400 rpm for 20 min at 65 °C and atmospheric pressure. Then, commercially available spherical alumina with KH-560 surface treatment was added in batches of 20 parts each time, and stirred for 10 min after each addition. After all the additions were completed, the planetary mixer was evacuated to -0.097 MPa and stirred at 600 rpm for 1.5 h under vacuum. After cooling to room temperature, the material was discharged, sealed and packaged to obtain Component B. Component A and component B are mixed at a weight ratio of 1:1.5 to obtain the low-viscosity, high-strength two-component polyurethane thermally conductive potting compound.
[0034] Example 3 A low-viscosity, high-strength two-component polyurethane thermally conductive potting compound, comprising the following components in parts by weight: Includes component A and component B; Component A comprises the following components in parts by weight: 80 parts of carbodiimide-urea-ketimide modified MDI (NCO content approximately 29.5%, viscosity at 25°C 60 mPa·s, Wanhua MDI-100LL); 20 parts of polypropylene glycol (molecular weight 700, hydroxyl value 160 mgKOH / g, viscosity at 25°C 200 mPa·s); and 0.3 parts of antioxidant 1010. Component B comprises the following components in parts by weight: 35 parts of polypropylene glycol (molecular weight 600, hydroxyl value 187 mgKOH / g, viscosity 210 mPa·s at 25℃); 15 parts of phthalic anhydride polyester glycol (molecular weight 600, hydroxyl value 187 mgKOH / g, viscosity 2500 mPa·s at 25℃); 10 parts of chain extender DETDA (amine value approximately 650 mgKOH / g, viscosity 150 mPa·s at 25℃); 80 parts of commercially available spherical alumina (D50=10μm, purchased from Suzhou Sanrui Baide New Materials Co., Ltd.) surface-treated with KH-560; 0.1 parts of organic bismuth catalyst (bismuth neodecanoate, bismuth content 23%); and 0.3 parts of organosilicon defoamer (BYK-530).
[0035] A method for preparing a low-viscosity, high-strength two-component polyurethane thermally conductive potting compound includes the following steps: Preparation of Component A: Under dry nitrogen protection, carbodiimide-urea ketimide modified MDI and antioxidant 1010 were added to the reactor. The temperature was raised to 50°C and stirred evenly. Under continuous stirring, polyoxypropylene glycol that had been vacuum dehydrated at 110°C for 1.5 h was slowly added dropwise. After the addition was complete, the system temperature was raised to 75°C and the reaction was carried out for 2.5 h. The mixture was then cooled to below 40°C, discharged, and sealed in packaging to obtain Component A. Preparation of Component B: Under vacuum conditions, polypropylene glycol, phthalic anhydride polyester glycol, chain extender DETDA, bismuth neodecanoate and BYK-530 were added to a planetary mixer and stirred at 400 rpm for 20 min at 65 °C and atmospheric pressure. Then, commercially available spherical alumina with KH-560 surface treatment was added in batches of 20 parts each time, and stirred for 10 min after each addition. After all the additions were completed, the mixer was evacuated to -0.097 MPa and stirred at 600 rpm for 1.5 h under vacuum. After cooling to room temperature, the material was discharged, sealed and packaged to obtain Component B. Component A and component B are mixed at a weight ratio of 1:1.5 to obtain the low-viscosity, high-strength two-component polyurethane thermally conductive potting compound.
[0036] Example 4 A low-viscosity, high-strength two-component polyurethane thermally conductive potting compound, comprising the following components in parts by weight: Includes component A and component B; Component A comprises the following components in parts by weight: 80 parts of PAPI (NCO content approximately 31.0%, viscosity 250 mPa·s at 25°C, Wanhua PM-200); 20 parts of polypropylene glycol (molecular weight 700, hydroxyl value 160 mgKOH / g, viscosity 200 mPa·s at 25°C); and 0.3 parts of antioxidant 1010. Component B comprises the following components in parts by weight: 35 parts of polypropylene glycol (molecular weight 600, hydroxyl value 187 mg KOH / g, viscosity 210 mPa·s at 25℃); 15 parts of bisphenol A type polyether glycol; 10 parts of chain extender DETDA (amine value approximately 650 mg KOH / g, viscosity 150 mPa·s at 25℃); 80 parts of commercially available spherical alumina (D50=10μm, purchased from Suzhou Sanrui Baide New Materials Co., Ltd.) surface-treated with KH-560; 0.1 parts of organic bismuth catalyst (bismuth neodecanoate, bismuth content 23%); and 0.3 parts of organosilicon defoamer (BYK-530).
[0037] The synthesis method of the bisphenol A type polyether glycol is as follows: 228 parts by weight of bisphenol A and 1.0 parts by weight of KOH are added to a high-pressure reactor. After nitrogen purging, the temperature is raised to 120°C. 116 parts by weight of propylene oxide (molar ratio of bisphenol A:propylene oxide = 1:2) are added in batches. The pressure is controlled to be ≤0.4MPa. The reaction is carried out until the pressure no longer decreases. The mixture is cooled to 80°C, neutralized with phosphoric acid, filtered to remove potassium salt, and then dehydrated under vacuum at 110°C and -0.095MPa for 2 hours to obtain bisphenol A type polyether glycol (hydroxyl value 172 mgKOH / g, molecular weight 652, viscosity at 25°C 520 mPa·s).
[0038] A method for preparing a low-viscosity, high-strength two-component polyurethane thermally conductive potting compound includes the following steps: Preparation of Component A: Under dry nitrogen protection, carbodiimide-urea ketimide modified MDI and antioxidant 1010 were added to the reactor. The temperature was raised to 50°C and stirred evenly. Under continuous stirring, polyoxypropylene glycol that had been vacuum dehydrated at 110°C for 1.5 h was slowly added dropwise. After the addition was complete, the system temperature was raised to 75°C and the reaction was carried out for 2.5 h. The mixture was then cooled to below 40°C, discharged, and sealed in packaging to obtain Component A. Preparation of Component B: Under vacuum conditions, polypropylene glycol, bisphenol A type polyether glycol, chain extender DETDA, bismuth neodecanoate and BYK-530 were added to a planetary mixer and stirred at 400 rpm for 20 min at 65 °C and atmospheric pressure. Then, commercially available spherical alumina surface-treated with KH-560 was added in batches of 20 parts each time, and stirred for 10 min after each addition. After all the additions were completed, the mixer was evacuated to -0.097 MPa and stirred at 600 rpm for 1.5 h under vacuum. After cooling to room temperature, the material was discharged, sealed and packaged to obtain Component B. Component A and component B are mixed at a weight ratio of 1:1.5 to obtain the low-viscosity, high-strength two-component polyurethane thermally conductive potting compound.
[0039] Comparative Example 1 Referring to Example 1, the difference from Example 1 is that: bisphenol A type polyether glycol is not added to component B, but polyoxypropylene glycol is added instead, that is, 50 parts by weight of polyoxypropylene glycol is added.
[0040] Comparative Example 2 Referring to Example 1, the difference from Example 1 is that no thermally conductive filler is added to component B.
[0041] Comparative Example 3 Referring to Example 1, the difference from Example 1 is that the thermally conductive filler added to component B is ordinary spherical alumina (D50=10μm) without surface treatment.
[0042] Comparative Example 4 Referring to Example 1, the difference from Example 1 is that the chain extender DETDA in component B is replaced with MOCA (3,3'-dichloro-4,4'-diaminodiphenylmethane), as follows: Preparation of Component B: By weight, 10 parts of MOCA (solid) were melted in an oven at 120°C and kept warm for later use. Under vacuum conditions, 35 parts of polypropylene glycol, 15 parts of bisphenol A type polyether glycol (same as in Example 1), 0.1 parts of bismuth neodecanoate, and 0.3 parts of BYK-530 were added to a planetary mixer and stirred at 65°C and atmospheric pressure for 20 minutes. Then, 80 parts of commercially available spherical alumina with KH-560 surface treatment were added in batches. During the stirring process, molten MOCA was slowly added (keeping the temperature >100°C to prevent solidification). After all the MOCA was added, the planetary mixer was evacuated to -0.097 MPa and stirred at 600 rpm for 1.5 hours under vacuum. The mixture was then cooled to room temperature and discharged to obtain Component B.
[0043] Comparative Example 5 Referring to Example 1, the difference from Example 1 is that: polypropylene glycol is not added to component B, but is replaced by bisphenol A type polyether glycol (same as Example 1), that is, 50 parts by weight of bisphenol A type polyether glycol (same as Example 1) is added.
[0044] Comparative Example 6 Referring to Example 1, the difference from Example 1 is that the polypropylene glycol (molecular weight 600, hydroxyl value 187 mgKOH / g, viscosity 210 mPa·s at 25°C) in component B is replaced with polypropylene glycol (molecular weight 1000, hydroxyl value 112 mgKOH / g, viscosity 550 mPa·s at 25°C).
[0045] Comparative Example 7 Referring to Example 1, the difference from Example 1 is that the liquefied MDI in component A is replaced with toluene diisocyanate (TDI, grade T-100, NCO content of about 48%, viscosity of about 3 mPa·s at 25°C).
[0046] Performance testing: 1. Mixed viscosity: Referring to GB / T 2794-2022, the components A and B prepared in the examples and comparative examples were mixed separately, and the viscosity within 5 minutes after mixing was measured using a rotational viscometer at 25°C.
[0047] 2. The potting compounds prepared in the examples and comparative examples (Comparative Example 4 required preheating to 60°C for mixing due to the presence of crystalline particles in component B) were vacuum degassed and then poured and cured (first cured at 80°C for 3 hours, then cured at 120°C for 2 hours) to form specimens: Shear strength: Refer to GB / T 7124-2008, aluminum-aluminum lap joint test specimen.
[0048] Thermal conductivity: Refer to ASTM E1461-13 (2022), laser flash method.
[0049] Shear strength retention rate after 2000 hours of aging at 85℃ / 85% RH: The shear strength retention rate was tested after aging the shear specimens in an 85℃ / 85% RH constant temperature and humidity chamber for 2000 hours.
[0050] Tensile strength and elongation at break: Refer to GB / T 528-2009.
[0051] The test results are shown in Table 1.
[0052] Table 1 Test data results of the examples and comparative examples
[0053] As can be seen from the test results in Table 1, the overall performance of the examples is superior to that of the comparative examples, achieving a good balance between mixed viscosity, shear strength, thermal conductivity, and 85% aging retention rate. Comparative Example 1 lacks a rigid reinforcing component, resulting in a significant decrease in shear strength; Comparative Example 2 has no filler, resulting in extremely low thermal conductivity; Comparative Example 3 has filler without surface treatment, leading to a dramatic increase in viscosity; Comparative Example 4 uses MOCA solid chain extender, which not only requires heating and melting but also causes component B to easily crystallize and precipitate at room temperature, resulting in poor process stability, and its 85% aging retention rate (81%) is significantly lower than that of Example 1 (89%), failing to meet the core requirement of this invention for long-term damp heat reliability. Comparative Example 5 completely lacks low-viscosity polyether polyol B, resulting in excessively high system viscosity that prevents potting; Comparative Example 6, after replacing low-viscosity polyether polyol B with ordinary polyether with a molecular weight of 1000, saw the mixed viscosity rise to 2650 mPa·s and the shear strength drop to 9.8 MPa; Comparative Example 7, after replacing with TDI, although the viscosity is low, suffers from severe bubbling, an elongation of only 52%, and an aging retention rate of only 70%. The above comparative examples demonstrate from different perspectives that this invention achieves low viscosity (≤2100 mPa·s), high shear strength (≥11.2 MPa), high thermal conductivity [≥1.2 W / (m·K)], and excellent resistance to damp heat aging (retention rate ≥78%) through a synergistic combination of liquefied MDI, low-viscosity polyether polyol B, bisphenol A type polyether diol, DETDA, and commercially available spherical alumina surface-treated with KH-560. In summary, the low-viscosity, high-strength two-component polyurethane thermally conductive potting compound prepared by this invention can meet the comprehensive requirements of high-power electronic devices for potting compounds.
[0054] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A low-viscosity, high-strength two-component polyurethane thermally conductive potting compound, characterized in that, Includes component A and component B; Component A comprises the following components in parts by weight: 70-90 parts of polyisocyanate, 10-30 parts of polyether polyol A, and 0.1-0.5 parts of antioxidant; Component B comprises the following components in parts by weight: 25-45 parts of low-viscosity polyether polyol B, 10-20 parts of rigidity-reinforcing polyol, 5-15 parts of chain extender, 60-120 parts of thermally conductive filler, 0.05-0.2 parts of catalyst, and 0.1-0.5 parts of defoamer.
2. The low-viscosity, high-strength two-component polyurethane thermally conductive potting compound according to claim 1, characterized in that, The polyisocyanate is selected from at least one of liquefied diphenylmethane diisocyanate (MDI), polyphenylmethylene polyisocyanate, and toluene diisocyanate.
3. The low-viscosity, high-strength two-component polyurethane thermally conductive potting compound according to claim 2, characterized in that, The liquefied diphenylmethane diisocyanate MDI is a carbodiimide-urea ketimide modified MDI, a carbamate modified MDI, or a prepolymer modified MDI.
4. The low-viscosity, high-strength two-component polyurethane thermally conductive potting compound according to claim 1, characterized in that, The polyether polyol A is selected from at least one of polypropylene oxide diol, polytetrahydrofuran ether diol, and polyethylene oxide-propylene oxide copolyether diol.
5. The low-viscosity, high-strength two-component polyurethane thermally conductive potting compound according to claim 1, characterized in that, The low-viscosity polyether polyol B is selected from at least one of polyoxypropylene glycol and polyoxypropylene triol.
6. The low-viscosity, high-strength two-component polyurethane thermally conductive potting compound according to claim 1, characterized in that, The rigidity-reinforced polyol is selected from at least one of bisphenol A type polyether diol, bisphenol S type polyether diol, and phthalic anhydride polyester diol.
7. The low-viscosity, high-strength two-component polyurethane thermally conductive potting compound according to claim 6, characterized in that, The bisphenol A type polyether diol is prepared by ring-opening polymerization of bisphenol A and epoxide under an alkaline catalyst; the molecular weight of the bisphenol A type polyether diol is 500-800, the hydroxyl value is 140-225 mgKOH / g, and the viscosity at 25℃ is 400-600 mPa·s.
8. The low-viscosity, high-strength two-component polyurethane thermally conductive potting compound according to claim 1, characterized in that, The chain extender is selected from at least one of diethyltoluenediamine (DETDA), dimethylthiotoluenediamine (DMTDA), and 1,4-butanediol (BDO).
9. The low-viscosity, high-strength two-component polyurethane thermally conductive potting compound according to claim 1, characterized in that, The thermally conductive filler is selected from at least one of spherical alumina, angular alumina, aluminum nitride, boron nitride, and zinc oxide that have been surface-treated with a silane coupling agent; the catalyst is selected from at least one of organobismuth catalysts and organotin catalysts; and the defoamer is selected from at least one of organosilicon defoamers and polyether defoamers.
10. The method for preparing the low-viscosity, high-strength two-component polyurethane thermally conductive potting compound according to any one of claims 1 to 9, characterized in that, Includes the following steps: Preparation of component A: Under dry nitrogen protection, add polyisocyanate and antioxidant to the reaction vessel, heat to 50±5℃ and stir evenly. Under continuous stirring, add polyether polyol A that has been vacuum dehydrated at 110±5℃ for 1.5-2h. After the addition is complete, raise the system temperature to 75±5℃, react for 2-3h, cool, discharge, seal and package to obtain component A. Preparation of Component B: Under vacuum conditions, low-viscosity polyether polyol B, rigid-reinforcing polyol, chain extender, catalyst and defoamer are added to a planetary mixer and stirred and mixed evenly at 60-70℃ and normal pressure. Then, thermally conductive filler is added in batches, and stirred evenly after each addition. After all the filler has been added, the planetary mixer is evacuated to -0.098MPa to -0.095MPa and stirred and mixed under vacuum for 1-1.5h. After cooling to room temperature, the material is discharged, sealed and packaged to obtain Component B. Component A and component B are mixed at a weight ratio of 1:1-3 to obtain the low-viscosity, high-strength two-component polyurethane thermally conductive potting compound.